Polinômios de permutação e q-polinômios - Sousa, João Paulo Guardieiro (2021)
In this work, we discuss some results involving permutation polynomials and q-polynomials, both defined over finite fields. Firstly we introduce basic concepts and theorems concerning each one of those polynomials classes. Then, we find criteria to determinate if a given q-polynomial is a permutation one and study two methods in order to obtain q-polynomials which already have this property. At the end of this dissertation, we will apply the results obtained previously in order to find conditions under which a specific polynomial class can be planar.